Potential therapeutic use of cannabinoid compounds - cannabidiol and delta-9-tetrahydrocannabinol (Research, Society and Development, 2021)
Derivatives of Cannabis sativa are being used to treat comorbidities that do not yet have an efficient treatment for damage and symptoms. The cannabinoid compounds - cannabidiol and delta-9-tetrahydrocannabinol have been tested for therapeutic use and several studies seek to elucidate the pharmacological effects of these substances. Thus, the present study gathers information on cannabinoid derivatives and the pharmacological effects already described for the cannabidiol and delta-9-tetrahydrocannabinol compounds. An integrative literature review was performed based on data collected from original articles obtained from the databases: MEDLINE, SciELO, BVS and LILACS, using the terms: cannabinoids, cannabidiol, tetrahydrocannabinol (dronabinol), medical marijuana. Knowledge about endocannabinoid ligands demonstrates that cannabinoid compounds can play a significant role in mediating several neurophysiological processes. Research shows that these derivatives are an important alternative for the treatment of various pathologies, mainly on diseases that still do not have a response or that the response is not as effective. Data reinforce that cannabinoids can be a therapeutic option for patients undergoing chemotherapy assisting in crises resulting from treatment, in addition to assisting in the treatment of spinal trauma, AIDS, multiple sclerosis, peripheral neuropathy, Tourette's syndrome, in the postoperative period - cerebral infarction or other clinical conditions that have a strong association with chronic pain. Although scientific advances demonstrate benefits in the use of cannabinoid compounds, there is still a need for studies to prove the action. Research with Cannabis sativa opens space for the possibility of treating diseases that do not yet have a therapeutic response, making these substances a pharmaceutical hope.